Black Chokeberry (Aronia melanocarpa (Michx.) Elliot) Fruits and Functional Drinks Differ Significantly in Their Chemical Composition and Antioxidant Activity. (1st November 2018) - Denev, Petko; Kratchanova, Maria; Petrova, Ivalina; Klisurova, Daniela; Georgiev, Yordan; Ognyanov, Manol; Yanakieva, Irina
Abstract : Black chokeberry ( Aronia melanocarpa ) fruits are among the richest sources of polyphenols and anthocyanins in plant kingdom and suitable raw material for production of functional foods. The popularity of chokeberries is not only due to their nutritional value but also to the constantly emerging evidence for their health-promoting effects. The current study presents detailed information about the content and composition of sugars, organic acids, and polyphenols in 23 aronia samples grown under the climatic conditions of Bulgaria, in 2016 and 2017. Sorbitol was found to be the main carbohydrate of fresh aronia fruits. Its content was in the range 6.5–13 g/100 g fresh weight (FW), representing 61%–68% of low-molecular-weight carbohydrates. Organic acids were represented by substantial amounts of quinic acid (average content 404.4 mg/100 g FW), malic acid (328.1 mg/100 g FW), and ascorbic acid (65.2 mg/100 g FW). Shikimic acid, citric acid, oxalic acid, and succinic acid were found as minor components. Chokeberries were particularly rich in proanthocyanidins, anthocyanins, and hydroxycinnamic acids. The total polyphenol content of aronia fruits varied between 1022 mg/100 g FW and 1795 mg/100 g FW and ORAC antioxidant activity from 109  µ mol TE/g to 191  µ mol TE/g FW. We also investigated the relationship between the chemical composition of berries and chemical compositions and antioxidant activity of aronia functional drinks—juices and nectars. The differences in the chemical composition of the fruits resulted in functional foods that differ significantly in their chemical composition and antioxidant activity. Additionally, we demonstrated that temperature of juice pressing and nectar extraction has a profound effect on the polyphenol content and composition of these products. This is very important since differences in the chemical composition of raw chokeberries and variation of technological parameters during processing could result in functional foods with different chemical composition, rendering different biological activity.